Challenges and barriers faced by the young generation involved in trade unions - Ismail, Fadillah; Wei, Chan Shiau; Sern, Jared Tan Yu (Journal of Islamic, Social, Economics and Development, 2026)
In an increasingly volatile labour market, trade unions remain a key mechanism for safeguarding young workers’ rights, welfare, and fair treatment at work. This paper synthesises key literature to explain why youth participation in trade unions remains limited and what can be done to strengthen engagement. The discussion identifies four recurring barriers: job instability and short-term employment that weakens union coverage; limited knowledge and exposure to labour rights and union functions; persistent gender inequality that constrains participation, especially among young women; and negative or misleading narratives circulated through social media that undermine unions’ public image. Building on these insights, the paper highlights practical pathways to revitalise youth involvement, including modernising outreach via digital platforms, running targeted awareness campaigns through schools and higher education settings, and strengthening union credibility through trust-building and collaborative partnerships.